Sensing and Biosensing in the World of Autonomous Machines and Intelligent Systems - Oliveira, Osvaldo N.; Oliveira, Maria Cristina F. (Frontiers in Sensors, 2021)
In this paper we discuss how nanotech-based sensors and biosensors are providing the data for autonomous machines and intelligent systems, using two metaphors to exemplify the convergence between nanotechnology and artificial intelligence (AI). These are related to sensors to mimic the five human senses, and integration of data from varied sources and natures into an intelligent system to manage autonomous services, as in a train station.